2017
DOI: 10.1038/s41598-017-02358-z
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids ameliorate TGF-β1-mediated epithelial-to-mesenchymal transition of airway epithelium through MAPK and Snail/Slug signaling pathways

Abstract: Chronic rhinosinusitis with nasal polyps (CRSwNP) is closely associated with tissue remodeling. Epithelial-to-mesenchymal transition (EMT), a process of tissue remodeling, can be a therapeutic target of CRSwNP. Glucocorticoids are a type of steroid hormone that is used primarily in medical therapy for patients with CRSwNP; however, their effects on EMT in the airway epithelium remain unknown. To investigate the effects of dexamethasone and fluticasone propionate, a class of glucocorticoids, on transforming gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 44 publications
0
36
0
Order By: Relevance
“…Down regulation of E-cadherin and up regulation of N-cadherin are the major molecular events regarding the reduction in cell-cell adhesion and facilitation of cell movement [ 49 , 50 ]. In addition, vimentin is an important protein regulator of EMT and the down-regulation of vimentin has been shown to decrease cell migration and transcription factors of EMT, such as snail and slug [ 51 53 ]. In this study, we found that phoyunnanin E could reverse the E-cadherin to N-cadherin switch and reduce vimentin and the related EMT transcription factors, snail and slug (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Down regulation of E-cadherin and up regulation of N-cadherin are the major molecular events regarding the reduction in cell-cell adhesion and facilitation of cell movement [ 49 , 50 ]. In addition, vimentin is an important protein regulator of EMT and the down-regulation of vimentin has been shown to decrease cell migration and transcription factors of EMT, such as snail and slug [ 51 53 ]. In this study, we found that phoyunnanin E could reverse the E-cadherin to N-cadherin switch and reduce vimentin and the related EMT transcription factors, snail and slug (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…WB showed that STYK1 over-expression downregulated the expression of epithelial marker E-cadherin while it upregulated mesenchymal protein markers (Figure 8C ). Previous studies showed that p38 MAPK signaling pathway was correlated with EMT and involved in cancer progression [ 14 , 15 ]. We next focused on the p38 MAPK pathways.…”
Section: Resultsmentioning
confidence: 99%
“…The MAPK signaling pathway plays a role in EMT of the various kinds of epithelial cells and includes JNK, p38 MAPK, and ERK (Yang, Lee, & Shin, ; Zhang, Lian, & Liang, ; Zhang, Wang, & Fan, ). In order to assess the effect of mulberry leaves extracts on high glucose‐stimulated ERK1/2 activation, the expressions of phospho‐ERK1/2 were detected by western blot.…”
Section: Resultsmentioning
confidence: 99%